Development of low sodium salted eggs and its antioxidant potential - Setyaningrum Ariviani; Nur Hikmah Fitriasih; Dwi Ishartini (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2017)
ABSTRACTBackground: Salted egg is one of processed egg products which has a nutrient content that is comparable to the fresh egg, has a longer shelf life and can be consumed by all ages. The main process in the salted egg production is salting (NaCl) treatment that will give salty taste and acts as a preservative.Objectives: This study aimed to develop low-sodium salted eggs with an antioxidant potential through the innovations in the salting process.Methods: This was an experimental research. Salted eggs were produced with innovations in salting process using various concentration of teak leaf extract and potassium chloride (KCl) substitution. The sensory qualities of the salted eggs were determined using differential tests. Salted eggs with the best sensory quality were determined their nutritional quality with proximate measurements and their antioxidative potency by measuring total phenolic content and antioxidant activityResults: The research result showed that the KCl substitution did not affect the total phenolic content (TPC) of salted eggs, but it reduced the sensory qualities which include the quality of taste, color, flavor and overall. The addition of teak leaf extracts improved both the sensory quality and TPC of salted eggs produced with KCl substitutions. TPC  increased along with increased of teak leaf extract concentrations. KCl substitution or addition of teak leaves extract proved to increase the radical scavenging activity of salted eggs. The low-sodium salted egg with an antioxidant potential which was made using selected salting formulation had nutritional and sensory qualities which comparable to the salted eggs produced using sodium chloride (NaCl)Conclusions: The low-sodium salted eggs have antioxidant potential that can be produced by salting process innovation using teak leaf extract and KCl substitution.KEYWORDS:  salted egg, KCl, teak leaf extracts, antioxidants, sensory